Islamic Education Thought Seyyed Naquib Al-Attas - Muhammad Syaiful Islam (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
This paper explains the concept of Islamic education originating from one of the Muslim scholars, Syed Muhammad Naquib al-Attas. His concept of Islamic education can be said to be fundamental. His concept was based on his thoughts on the Islamization of Science. Thus, al-Attas believes that the fundamental problem of Islamic education is the carelessness of people in formulating and developing educational plans based on integrated Islamic principles. Thus, he considered that the concept and pattern of notification of Islamic education lies in its system and purpose. He offered "ta'dib" as a term for the concept of education. The choice of this term has implications for the Islamic education system, including: objectives, forms, and curriculum.